Diagnostic value of non-invasive indices for assessing liver fibrosis in Chinese children with metabolic dysfunction-associated steatotic liver disease - Zhou, Juan; Liu, Min; Qiu, Jun; Ouyang, Wenxian; Zhu, Guanghui; Chen, Weijian; Li, Shuangjie; Zhao, Hongmei (Frontiers in Pediatrics, 2026)
Introduction and objectivesThe rising prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD) in Chinese children necessitates non-invasive fibrosis assessment. However, there is a paucity of pediatric-specific diagnostic tools. The objective of this study was to evaluate the performance of seven established non-invasive indices for staging liver fibrosis in Chinese children with biopsy-proven MASLD.Materials and methodsA cross-sectional analysis was conducted in children with MASLD. Liver fibrosis staging (F0-F4) was determined via histological assessment. The diagnostic performance of seven non-invasive indices (APRI, FIB-4, PNFI, TyG, AAR, API, NFS) was evaluated using Spearman correlation analysis and area under the receiver operating characteristic curve (AUROC) analysis.ResultsA total of 110 children were included in the study, among whom significant fibrosis (F ≥ 2) was present in 36.3% (40/110), including 12.7% with F3 and 2.7% with cirrhosis (F4). When analyzing the correlations between indices and fibrosis stages, only modest positive correlations were observed for APRI (r = 0.32), FIB-4 (r = 0.23), PNFI (r = 0.24) and TyG (r = 0.24) (all P < 0.05), while AAR, API and NFS had no significant correlations (all P > 0.05). All indices exhibited poor diagnostic accuracy, with AUROCs ranging from 0.49 to 0.69 across all fibrosis stages. Specifically, APRI, FIB-4 and TyG showed analogous AUROCs (0.60–0.69) for diagnosing any (F ≥ 1), significant (F ≥ 2) and severe (F ≥ 3) fibrosis. Conversely, AAR, API and NFS demonstrated even poorer performance, with AUROCs ranging from 0.49 to 0.60.ConclusionThe non-invasive fibrosis indices that have been validated demonstrated poor diagnostic accuracy and unreliable performance in Chinese children with MASLD. This diagnostic gap emphasizes the urgent need for the development of pediatric-specific diagnostic algorithms tailored for MASLD-related liver fibrosis.